Facing FoMO through Prophetic Wisdom: Hadith-Based Strategies for Digital Calm - Nihayatul Ismil Fadhilah; Ahmad Atabik; Arif Friyadi (UIN Syarif Hidayatullah Jakarta, 2025)
The phenomenon of FoMO has become increasingly common in today’s digital era. It negatively affects mental health by causing anxiety, restlessness, and fear of being left behind in trends, information, or social experiences. This article examines FoMO through the lens of the Prophet Muhammad’s hadiths, which offer spiritual and moral guidance in Islam. Using a qualitative method with a descriptive-analytical approach, this study reviews Islamic literature especially hadith collections and relevant scholarly works. The analysis centers on the values of contentment , patience , trust in God, asceticism, modesty, and how these teachings can be applied in modern contexts. The study finds that these values help reduce the negative impact of FoMO, build stronger mental and spiritual resilience, and support emotional well-being. In conclusion, the moral wisdom contained in the hadith offers meaningful solutions to preserve mental health and inner peace amid the fast-paced, competitive nature of today’s digital world.